Cremanthodium liangshanicum (Asteraceae, Senecioneae), a new species from southwestern Sichuan, China - Wang, Long; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2016)
Cremanthodium liangshanicum (Asteraceae, Senecioneae), a new species from the Liangshan Mountains region in southwestern Sichuan, China, is illustrated and described. The new species is similar to C. potaninii and C. cyclaminanthum in habit and the relatively smaller leaves, but differs from both of them in the stem pubescence and the shape of the basal leaves. From the former it can be distinguished additionally by the phyllary indumentum, and particularly, by the shape and length of the ray laminae. From the latter it is distinct also in the shape of the involucres and the length of the pappus.